PRE MARITAL TEENAGE SEX BEHAVIOUR (Study at Buru District Karimun Regency) - ", Nurhafiza; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was held in the district Buru district of Karimun. The purpose of this study is to know to know and describe the factors that cause premarital sex behavior by teenagers in Buru district. Topic of focus of this research is the view of society in premarital sex behavior among youth district Buru. The author uses qualitative methods and uses the snowball sampling technique technique. Data instruments are observations, interviews, polls and documentation. Research finds there are three factors that encourage the occurrence of premarital sex by teenagers, as follows: Family factor, research finds that families are less considerate and do not control how children's lives outside the home. So the child feels freed by his parents to establish a relationship with anyone. Social environmental factors, research finds that research subjects often gather to stay in their friends for days. To facilitate premarital sex irregularities by the child. The factors of information technology, the research conducted found that generally young children are researched to know their spouse from social media. Then the factor of information technology has a crucial role in child-free sex irregularities.  Research conducted there are some forms of premarital sex by teens is embracing, hugging and kissing.Keywords: Premarital, Teenage, Social Deviations